Case Report: Recurrent Keloid Excision with Tension Reduction Suture and Adjuvant Closed Incision Negative Pressure Wound Therapy - Ananda Rahmadanti Perdanakusuma; David Sontani Perdanakusuma (The International Journal of Medical Science and Health Research, 2025)
Background: Keloid management presents significant clinical challenges due to the very high recurrence rate after single surgical excision, reported to reach 50-100%. This failure is primarily caused by mechanical tension on the post-closure wound, which reactivates the fibroproliferative cascade. Closed Incision Negative Pressure Wound Therapy (ciNPWT) emerges as a promising adjuvant therapy because it directly targets this mechanical tension. This case report aims to present the effectiveness of a combination of excision, tension reduction sutures, and ciNPWT in high-risk recurrent keloids. Methods: A 16-year-old male patient with a recurrent keloid on the right upper arm underwent a wide excision procedure and tension reduction suture technique. After wound closure, a ciNPWT dressing was applied over the incision line and connected to a portable device. Continuous negative pressure therapy of −125 mmHg was maintained for 7 days post-operation. Results: The surgical procedure and post-operative care proceeded smoothly without complications such as infection or wound dehiscence. After 7 days, the surgical wound appeared clean and tightly closed with minimal edema. At the 3-month follow-up, the scar appeared calm, flat, and aesthetic, with no clinical signs of keloid recurrence. The patient reported high satisfaction and resolution of itching complaints. Discussion: The success of managing this case strongly validates the fundamental theory that mechanical tension is the primary trigger for keloid recurrence. The applied approach—through surgical excision followed by a tension reduction suture technique—directly targets this crucial factor. Furthermore, the application of ciNPWT as an adjuvant therapy functions as an effective external "mechanical splint." Its role is to neutralize residual tension on the wound and actively disrupt the profibrotic mechanotransduction cascade that triggers fibrosis. This mechanomodulatory strategy fundamentally addresses the root cause of keloid pathology, offering significant advantages over other adjuvant therapies that do not directly and specifically target the tension factor. Conclusion: The combination of surgical excision, tension reduction suture technique, and adjuvant ciNPWT application proved to be a highly effective and rational management strategy for recurrent keloids. This multimodal approach successfully addresses the tension factor—identified as the primary etiology—thus precisely breaking the recurrence cycle. By fundamentally targeting its root cause, this strategy can be a superior therapeutic option for cases with a high risk of recurrence.